The safety and efficacy of balloon-expandable versus self-expanding trans-catheter aortic valve replacement in high-risk patients with severe symptomatic aortic stenosis - Senguttuvan, Nagendra Boopathy; Bhatt, Hemal; Balakrishnan, Vinod Kumar; Krishnamoorthy, Parasuram; Goel, Sunny; Reddy, Pothireddy M. K.; Subramanian, Vinodhini; Claessen, Bimmer E.; Kumar, Ashish; Majmundar, Monil; Ro, Richard; Lerakis, Stamatios; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aim Transfemoral Trans-catheter Aortic Valve Replacement (TF-TAVR) is a safe and effective therapy compared with surgical aortic valve replacement (SAVR) in patients across all risk profiles using balloon-expandable valves (BEV) and self-expanding valves (SEV). Our aim was to compare safety and efficacy of BEV vs. SEV in high-risk patients undergoing TF-TAVR. Methods and results We searched PubMed, EMBASE, Clinicaltrials.gov, Scopus, and Web of sciences for studies on patients with severe aortic stenosis undergoing TAVR. Primary outcome was 30-day all-cause mortality. Secondary outcomes defined by Valve Academic Research Consortium 2 (VARC-2) criteria were also examined. Six studies with 2,935 patients (1,439 to BEV and 1,496 to SEV) were included. BEV was associated with lower risk of all-cause mortality (2.2% vs. 4.5%; RR: 0.51; 95% CI: 0.31–0.82; p < 0.006) and cardiovascular mortality [(2.5% vs. 4.3%; RR: 0.54; 95% CI: 0.32–0.90; p = 0.01) at 30 days compared with SEV. Implantation of more than one valve per procedure (0.78% vs. 5.11%; RR: 0.15; 95% CI: 0.07–0.31; p < 0.00001), and moderate/severe AR/PVL (2.5% vs. 9.01%; RR: 0.3; 95% CI: 0.17–0.48); p < 0.00001) were also lower in the BEV arm. Conclusion BEV TAVR is associated with reduced all-cause mortality (High level of GRADE evidence), cardiovascular mortality (very low level) at 30 days compared with SEV TAVR in high surgical risk patients. Data are necessary to determine if the difference in outcomes persists in longer-term and if the same effects are seen in lower-risk patients. Systematic Review Registration identifier, CRD42020181190.